Establishment of microbiota in larval culture of Pacific oyster, Crassostrea gigas - Asmani, Katia; Petton, Bruno; Le Grand, Jacqueline; Mounier, Jerome; Robert, Rene; Nicolas, Jean-louis (Aquaculture, 2016)
This study has two main objectives: (1) to implement a recycling aquaculture system (RS) for the larvae of the oyster Crassostrea gigas, and (2) to characterise the bacterial communities established in different compartments of this system. An RS with 25% fresh seawater addition per hour and another with no addition (0%) were compared with a flow-through system (FT). Larval survival was equivalent in RS and FT, but growth rate was 17% slower in RS than in FT. The physical chemical parameters remained stable, except for pH that decreased to 7.75 and salinity that increased to 37.5‰ in the RS 0%. In both systems, the cultivable bacteria were present in similar numbers in seawater (around 105 ml− 1) and in larvae (103 larva− 1) on day 15. Bacterial assemblages, characterised by 454 pyrosequencing of the V1–V3 region of 16S rRNA, were highly similar (50–65%) for compartments, regardless of rearing system and sampling time, but the compartments were clearly different from one another. At the beginning of rearing, larval microbiota was mostly composed of Proteobacteria (~ 90%), with 47% Rhodobacteraceae (α-Proteobacteria). γ-Proteobacteria, including Pseudoalteromonas, Alteromonas and a few vibrios, declined in the rearing period (25% on day 7 to 9% on day 15). At the end of rearing, colonisation by two members of the Burkholderiales (β-Proteobacteria), 45% on average on day 15, had decreased overall diversity. Seawater microbiota was more stable with in all batches as one unclassified bacterium present in all batches (27 ± 7%), 42 OTUs of α-Proteobacteria (19 ± 7%) and 26 of γ-Proteobacteria (14%). Change was due notably to a species of Cryomorphaceae (Flavobacteria) that reached 15 ± 7% on day 15. Predatory bacteria, Bdellovivrio spp. and Bacteriovorax spp. were present (3–12%) and could participate in the regulation of bacterial populations. Bacterial assemblages in RS bioreactors remained stable and were mainly composed of Rhodobacteraceae, Rhizobiales and Planctomycetes. Only a few nitrite oxidisers were detected ...